A149 DEVELOPING, EVALUATING, AND DISSEMINATING KNOWLEDGE TRANSLATION RESOURCES TO ANSWER PATIENT QUESTIONS ABOUT IBD AND ITS MANAGEMENT. (1st March 2018) - Walker, J R; Targownik, L E; Bernstein, M T; Haviva, C; Graff, L A; Restall, G; Singh, H; El-Matary, W; Vagianos, K; Thomson, P; Bernstein, C N
Abstract: Background: Previous research by our team indicates that patients and their families have many questions about IBD that are not fully answered by existing resources. Aims: To describe the development, evaluation, and dissemination of education resources for persons with IBD. Methods: Previous research identified questions that are important to persons with IBD – close to the time of diagnosis or after having the condition for many years. We developed a patient and family advisory committee to assist us in developing resources. Individual fact sheets were created to address specific questions using existing research evidence and language that can be understood by patients and family members. Results: A wide range of concise fact sheets were developed covering important topics such as: new diagnosis of IBD, diagnostics in IBD, risk factors, common treatments (fact sheets for major classes – 5 ASA, thioprines, corticosteroids, biologics), managing cost of medications, insurance coverage for IBD medication, nutrition and IBD, antibiotics, probiotics, herbal medicines, marijuana and IBD, IBD and pregnancy, and IBD in childhood and adolescence. In addition to evaluation by the Patient and Family Advisory Committee, we collaborated with Crohn's and Colitis Canada to evaluate the fact sheets through contacts with members of their organization and web-based surveys. The surveys evaluated each fact sheet a section at a time and participants rated the degree to which fact sheets had enough (vs. not enough or too much) information, offered familiar or unfamiliar information, were trustworthy, and clear and understandable. Survey participants were also provided space to suggest improvements. Additional fact sheets will be developed in the future using a similar development and evaluation approach. Conclusions: The fact sheets provide information in a convenient, understandable and accessible format that can be viewed electronically or downloaded for print. The fact sheets will be disseminated by Crohn's and Colitis Canada through their website and educational activities and have a Creative Commons copyright so they may be widely distributed in English and French versions. They will also be helpful to clinicians in providing clear information to their patients. Additional fact sheets on emerging topics will be developed following a similar approach. Involving the knowledge users in the development and assessment of education tools is key to optimizing knowledge translation. Samples of the fact sheets will be provided. Funding Agencies: CIHR